Development, implementation and practical application of a nutritional questionnaire for tennis athletes - Body, SD. (Journal of Australian Strength and Conditioning, 2013)
This article outlines the development of a nutritional questionnaire (tool) designed to assess the dietary intake, eating habits and patterns, training load and goals, exercise requirements of the sport, work/school/study commitments, health concerns and anthropometric data, using four competition tennis players as case studies. It goes through the process of collecting and analysing the data, as well as providing dietary recommendations for the athletes. The issue of on-going monitoring is also discussed. The physical requirements in tennis are examined as are the dominant energy systems used. Practical recommendations for the delivery, length (no more than 30 minutes), and content of the questionnaire are made. The questionnaire includes questions about the athlete`s medical history, sporting goals, living arrangements, issues regarding menstruation, daily food intake and activity, variety and frequency of foods that are eaten. Methods used for assessment are demonstrated and the resources used in gathering the data are referenced.